On the conditions of solvability and the resolvent of a second-order deferential boundary operator in a space of vector functions - Storozh, O. G. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
A boundary differential operator generated by the Sturm-Liouville differential expression with bounded operator potential and nonlocal boundary conditions is considered. The conditions for a considered operator to be a Fredholm and solvable operator are established and its resolvent is constructed.